Unintended convergence: how Finnish unemployment reached the European level - Erkki Koskela; Roope Uusitalo (Bank of Finland, 2004)
Finnish unemployment rose in the early 1990s from 3% to 18% in just four years.It has since fallen back to the average European level, being 9.0% in January 2003.In this paper, we describe the shocks leading to this unforeseen increase in unemployment.We then discuss and research the role of labour market institutions in the adjustment process that has brought unemployment back to a " normal " level.We argue that these institutions cannot be blamed for the increase in unemployment, but that more flexible institutions could have led to a more rapid fall in unemployment once the Finnish economy began to recover.
URN:NBN:fi:bof-20140807649
Keywords: 330; economic crisis; labour market institutions; unemployment